Technological capabilities, open innovation, and eco-innovation: Dynamic capabilities to increase corporate performance of SMEs - Luis Enrique Valdez-Juárez; Mauricio Castillo-Vergara (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Currently, small and medium enterprises (SMEs) play a leading role in most of the world's economies. For this reason, they seek technological competitiveness and improvement of their innovation activities. In this context, open innovation and eco-innovation are important elements to achieve these goals. With this background, the purpose of this paper is to analyze the relationship between technological capability, open innovation, and eco-innovation in corporate performance, testing a structural equation model using SmartPLS in a sample of 684 small and medium-sized companies in Mexico. The main results show that technological capability significantly influences open innovation and eco-innovation practices, not directly in corporate performance, but through open innovation or eco-innovation. Our results also confirm the positive effects that eco-innovation and open innovation have on SMEs' corporate performance. These results have important implications in the literature on dynamic capabilities that have not been previously tested. For companies and decision-makers, it shows why these practices in small and medium-sized companies should be encouraged.
Keywords: 650; open innovation; eco-innovation; SMEs; technological capabilities